Pelayanan Karyawan Terhadap Kepuasan Pelanggan Di Optik Tiara Jambi - Dolly iman suryanta; Rina novalinda (Jurnal Ekonomi dan Bisnis Digital, 2023)
This paper discusses employee service towards customer satisfaction at Optik Tiara Jambi. This study aims to describe employee service on customer satisfaction who come to Optik Tiara Jambi. Data was collected through questionnaires and interviews at Optik Tiara Jambi. Then the data is discussed based on the theory proposed in the literature review and presents the results of respondents' answers and interviews at Optik Tiara Jambi. The discussion is ordered based on the problem formulation. The research describes how the quality of employee service at Optik Jmabi affects customer satisfaction from June to August 2023. From the results of the interviews, it was found that 15 respondents (50%) were very satisfied and 15 respondents (50%) were satisfied with employee service at Optik Tiara Jambi, in This indicator is that employees carry out checks according to the SOP. Meanwhile, 21 respondents (70%) were very satisfied and 9 respondents (30%) were satisfied with efforts to improve service for customer satisfaction at Optik Tiara Jambi, one of the efforts made by employees to increase customer satisfaction was checking accurately and quickly. Based on the results of this research, there are several suggestions given to patients so that RO should be able to provide optimal service to customers so that customers feel comfortable and satisfied so that customers return to Optik to have their eyes checked.